Preparation and Education of Pupils at Primary School in Specific Safety Areas - Katarína KOŠÚTOVÁ; Linda MAKOVICKÁ OSVALDOVÁ; Jozef KUBÁS; Katarína HOLLÁ (Communications of International Proceedings, 2021)
Knowledge in field of safety is one of the most important pieces of information used in crisis situations. We get to them from an early age, when we are part of the education system, specifically in primary schools. The article deals with the current state of education in specific areas of safety for primary school students. These areas are civil protection, fire protection and first aid. The inquiry method - questionnaire - was used to verify the current state of education. Problematic fields of the educational process for pupils at selected primary schools in the Slovak Republic with regard to safety were identified on the basis of a survey of pupil’s opinions. Based on the law, the educational process in primary schools in the Slovak Republic is implemented as a two-level process, which enables primary schools to adapt the content of education according to specific regional requirements and the requirements of pupils and parents. In the educational process in primary schools, we can notice that theory is preferred over the practical use of theoretical knowledge. The main contribution of the article is to propose methodological measures to improve the level of education in the areas of civil protection, fire protection and first aid in the primary school environment.
Keywords: Education; Safety; Primary School; First Instance; Worksheet; Methodological Sheets; Human Resource; Civil Protection.